Finding the fuel poor and framing better policy - Palmer, J; Boardman, B; Terry, N; Fawcett, T; Narayan, U (Environmental Change Institute, University of Oxford, 2023)
The UK Government needs to make urgent decisions about whether and how to support more vulnerable energy users in the winter of 2023-24. The additional support provided in 2022-23 has been withdrawn, but prices continue to be very high, and in the absence of help, millions of households will struggle without adequate energy for heating, hot water, cooking and other vital services. This report uses data from smart-enabled prepayment meter customers to explore how the Government can best target support to those in greatest need, i.e. those in fuel poverty, and to describe the minimum level of support needed to prevent serious suffering this coming winter. This report is based on household energy consumption and other data for 11,519 households with dual-fuel gas and electricity supplies, provided by the energy company Utilita. Using data from four years, 2019-20 to 2022-23, analysis has looked at how energy use, rates and duration of self-disconnection have varied with external temperature, price, dwelling and household characteristics, and how policies and targeted payments affected energy use and self-disconnection.